PEMODELAN DISTRIBUSI AIR PANAS MENGGUNAKAN PROGRAM INVERSI DAMPED LEAST SQUARE PADA DATA VERTICAL ELECTRICAL SOUNDING DI DESA WAY MULI DAN KUNJIR - Petrus Waruwu (Jurnal Geosaintek, 2022)
The Mount Rajabasa area has several manifestations of hot springs that developed, one of which was in Way Muli and Kunjir Villages. The hot springs distributed layer in the area can be identified using the geoelectric resistivity vertical electrical sounding method. There were 3 sounding points of measurement results which were modelled in inversion using damped least squares. The purpose of this study was to determine the results of damped least square inversion modeling, determine subsurface lithology and model hot springs distribution by correlating 3 sounding points into 2-D transverse modelling. The results of data processing and modelling, there were 3 lithologies, namely top soil (14-466 m), sandstone (5-50 m) and clay (